COMPARISON TYPES OF CROUP: DIPHTERIC AND VIRAL CROUP (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article explores the multifaceted aspects of croup, a respiratory condition impacting young children. Distinguishing between viral and diphtheric croup is vital for accurate diagnosis and targeted medical intervention. Understanding the historical context and epidemiology aids in comprehensive insights. Diagnostic approaches for both types involve clinical evaluation, laboratory tests, and imaging. Reflecting on historical and current perspectives, this article emphasizes preventive measures, including vaccination, to mitigate the impact of these respiratory conditions on children.